2017
DOI: 10.1038/s41598-017-13577-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional SERS Substrates Formed with Plasmonic Core-Satellite Nanostructures

Abstract: We demonstrate three-dimensional surface-enhanced Raman spectroscopy (SERS) substrates formed by accumulating plasmonic nanostructures that are synthesized using a DNA-assisted assembly method. We densely immobilize Au nanoparticles (AuNPs) on polymer beads to form core-satellite nanostructures for detecting molecules by SERS. The experimental parameters affecting the AuNP immobilization, including salt concentration and the number ratio of the AuNPs to the polymer beads, are tested to achieve a high density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 71 publications
0
32
0
1
Order By: Relevance
“…By increasing the number of hotspots in the z-direction, the Raman signal can be increased and detection limits can be lowered. [41][42][43][44] Extrusion-based 3D printing is a direct deposition additive manufacturing approach that enables the layer-by-layer deposition of materials in x, y, and z to fabricate multilayer 3D structures. 3D printing has been used previously for the deposition of hydrogels and hydrogel-NP composites.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the number of hotspots in the z-direction, the Raman signal can be increased and detection limits can be lowered. [41][42][43][44] Extrusion-based 3D printing is a direct deposition additive manufacturing approach that enables the layer-by-layer deposition of materials in x, y, and z to fabricate multilayer 3D structures. 3D printing has been used previously for the deposition of hydrogels and hydrogel-NP composites.…”
Section: Introductionmentioning
confidence: 99%
“…1, it is shown that the HCP and monolayer structures are highly targeted as the initial and fundamental roughening factors to regularly tune the SERS hotspots in the created nanogaps. 23,49 Through the proposed structure, LSPRs were synergistically created from the collective electromagnetic elds from the entire AuIoNs structure. The roughness in atomic scale as presented as single adatoms or tiny clustered adatoms prominently leads to the occurrence of a short-range chemical enhancement mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…7, insets). It is known that the localized surface plasmon resonance of the nanoparticles can cause strong and highly localized fields for SERS (Wu, Li, Lin, & Chen, 2017). In this context, the distribution of the Ag-NPs was explored by TEM analysis.…”
Section: Samplementioning
confidence: 99%